Relationship Between the Self-Directed Learning Attitude, Academic Self-Efficacy, and Athlete Satisfaction in Korea College Athletes - Bumchul Chung; Wonchul Bing (SAGE Open)
Self-directed learning and self-efficacy have been well studied in education, but are lacking in the field of sports. Therefore, this cross-sectional study examined the association between self-directed learning attitudes, academic self-efficacy, and athlete satisfaction in collegiate athletes. Participants were 184 collegiate athletes, and data were collected using a questionnaire consisting of self-directed learning, self-efficacy, and athlete satisfaction scales. In addition, the study collected qualitative data from six additional athletes. Exploratory factor analysis and structural modeling were conducted to identify the factor structure of the preliminary scales, and confirmatory factor analysis was conducted to confirm the fit of the factor structure. The results showed that self-directed learning attitudes had a positive effect on academic self-efficacy and athlete satisfaction ( p  < .001). These findings highlight the importance of self-directed learning for college athletes and provide direction for college coaches in sports education.